The morality of knowledge in conversation - Stivers, Tanya; Mondada, Lorenza; Steensig, Jakob 1958-; Asmub, Brite; Enfield, N.J.; Hakulinen, Auli; Hayano, Kaoru; Heinemann, Trine; Heritage, John; Keevallik, Leelo; Kidwell, Mardi; Lindstrom, Anna; et al. (Cambridge Cambridge University Press, 2011)
This book demonstrates how we monitor others' rights to, and responsibilities for, knowledge in conversation, and their consequences for affiliation.
Introduction -- Affiliation consequences of managing epistemic asymmetries -- Epistemic resources for managing affiliation and alignment -- Toward a framework.
Includes bibliographical references and index.
Keywords: Conversation analysis; Knowledge, Theory of; Social interaction